Breast conserving surgery in the treatment of breast cancer stage III - D. V. Khaylenko; S. M. Portnoy; Yu. S. Egorov; V. A. Khaylenko (Опухоли женской репродуктивной системы, 2016)
This study evaluated the ability to perform organ-operation in breast cancer stage III. Highlight 2 similar groups of patients, depending on the extent of the procedure: in the 1st (main) were performed breast conserving surgery (BCS), in the 2nd (control) radical mastectomy (RM) with preservation of the pectoral muscles. It was analyzed overall survival (OS), disease-free survival (DFS); the frequency of postoperative complications and aesthetic results of the treatment. The 3-, 5- and 10-year OS group did not differ significantly and amounted to 80.0 ± 8.0, 87.0 ± 4.6 %; 70.2 ± 9.7, 67.8 ± 6.7 %; 61.4 ± 11.8, 62.2 ± 7.2 %, respectively (p > 0.05). The 3-, 5- and 10-year DFS group did not differ significantly and amounted to 68.1 ± 9.2, 80.7 ± 5.5 %; 58.9 ± 10.9, 67.2 ± 6.6 %; 58.9 ± 10.9, 60.3 ± 7.2 %), respectively (p > 0.05). The frequency of postoperative complications was in the group of BCS 7.7 %, in the group of RM – 6.9 % (p > 0.05). The aesthetic results of the treatment: satisfactory when BCS, unsatisfactory at RM.